UNICYSTIC AMELOBLASTOMA OF THE MANDIBLE - A CASE REPORT (International Journal of Food and Nutritional Sciences, 2023)
Ameloblastoma is a true neoplasm of odontogenic epithelial origin, with unicystic ameloblastoma being a subtype that comprises 5-15% of all intraosseous ameloblastomas. It's interesting to see its clinical and histological characteristics manifesting as a cystic lesion resembling a mandibular cyst but revealing ameloblastomatous epithelium upon examination. This case is of a 17-year-old male who adds to the body of literature on this condition.The fact that it's the second most common odontogenic neoplasm after odontoma highlights its clinical significance. Management of such cases often involves careful surgical intervention due to its tendency for recurrence and potential aggressive behavior.Understanding the nuances of different subtypes of ameloblastoma, like the unicystic variant, is crucial for accurate diagnosis and appropriate management. Such reports contribute significantly to the understanding and management of this condition.